Bcl-2-associated athanogene 3(BAG3) is associated with tumor cell proliferation, migration, invasion and chemoresistance in colorectal cancer - Li, Ning; Chen, Minghong; Cao, Yansha; Li, Hua; Zhao, Jinping; Zhai, Zhenhua; Ren, Fu; Li, Keyan (BMC cancer, 2018)
CRC is one of the most common malignancies worldwide, and its molecular mechanisms remain unclear. Elevated levels of BAG3 have been reported in various tumors. The present study aimed to explore the expression and function of BAG3 in CRC. BAG3 protein expression was evaluated in 90 CRC specimens using immunohistochemistry in tissue microarrays, and the correlation between BAG3 expression and the clinicopathological features were assessed. In HCT116 cells BAG3 overexpression cell models were constructed, and CRISPR/Cas9 was used for BAG3 knockout. Western blotting and quantitative real-time PCR were used to determine BAG3 expression in HCT-116 Cells. Cell proliferation, migration and invasion were analyzed by cell counting, colony formation assay, EdU cell proliferation assay, RTCA growth curve assays, wound-healing migration assay and transwell invasion assay. The influence of BAG3 expression level on chemoresistance in HCT-116 cells was examined. Gene expression microarray and IPA analyses were employed to explore signaling pathways associated with the control of BAG3. Using immunohistochemistry, this study found that BAG3 was markedly upregulated in colorectal cancer tissues and that BAG3 levels were significantly associated with tumor size and gender. BAG3 overexpression promoted HCT-116 cell growth, migration and invasion in vitro. In contrast, BAG3 knockout inhibited HCT-116 cell growth, migration and invasion. HCT-116 cells with high expression of BAG3 had higher cell viability and lower apoptosis rate than control cells after treatment with 5-FU, while the BAG3 knockout group demonstrated the opposite effects. So BAG3 expression level was associated with chemoresistance to 5-FU in HCT-116 cells. Gene expression microarrays and bioinformatics analyses of HCT-116 cells with BAG3 knockout demonstrated the involvement of BAG3 in signaling pathways associated with the control of cell proliferation, migration, invasion and chemoresistance in CRC. In conclusion, this study provided evidence that BAG3 has a relevant role in CRC biology, and defined potential molecular pathways and networks. So BAG3 may be considered as a potential therapeutic target for anti-tumor therapy in colorectal cancer.